Cross-flow structured packing for the process intensification of post-combustion carbon dioxide capture. (16th March 2018) - Lavalle, Gianluca; Lucquiaud, Mathieu; Wehrli, Marc; Valluri, Prashant
Highlights: A cross-flow cell of structured packing is inspected for carbon capture. Pressure drop and flow repartition are investigated numerically. The onset of flooding is shown to be delayed by tilting the cell. Abstract: We introduce novel insights into a cross-flow arrangement of structured packings specifically for post-combustion carbon dioxide capture. Gas-liquid dynamics are investigated numerically, with the liquid flowing under the action of the gravity and the gas driven by a horizontal pressure gradient crossing the liquid phase. An elementary packing cell consists of two connected channels: one depicting a co-current gas-liquid flow and the other depicting a counter-current two-phase flow. While flow reversal of the liquid phase can occur in the counter-flow channel at high gas flow rates, the overall flooding point is significantly delayed in comparison to a counter-current flow arrangement traditionally used for structured packings. Varying the gas flow rate and the tilting angle of the elementary cell, a detailed numerical analysis of the flow repartition between channels, the pressure drop, the gas and liquid velocities, and the onset of flooding is presented. The pressure drop is found to be smaller when tilting the cell with respect to the initial scenario at 45 ° . Flow reversal instead is delayed when lowering the tilting angle, that is when the cell is tilted anti-clockwise. We also reveal the presence of long waves at the edge of the cell at low tilting angles. Finally, data of the wet pressure drop in the cross-flow cell are compared with different commercially available types of packing arranged in a conventional vertical counter-flow configuration, such as several versions of the Sulzer Mellapak™.